Analysis of Influence of Different Heat Transfer Modes on Temperature Distribution in the Protective Clothing and Skin. (2016) - Łapka, Piotr; Furmański, Piotr; Wiśniewski, Tomasz S.
Abstract: Analyses of influence of different heat transfer modes on temperature distributions in the firefighter's multi-layer protective clothing, skin and muscle were carried out. The system under consideration was irradiated from an external source of thermal radiation and consisted of several fabrics separated by thin air gaps and the tissue made of several sublayers. Simulations were performed by applying the in-house 1D numerical model which accounted for coupled heat conduction and thermal radiation in the protective clothing with the associated phase transition of the bound water in fabric fibers and diffusion of water vapor in fabrics and air spaces as well as for heat conduction, thermal radiation and blood flow in the tissue. Complex thermal and mass transfer conditions at the internal and external boundaries were proposed. Special attention was paid to modelling of non-grey thermal radiation penetrating the clothing and being absorbed by the tissue. The results obtained were used to estimate influence of different heat transfer modes present in the system, on temperature distribution in the clothing and tissue and on variation of times needed to reach the I, II and III degree burns.